Analisis Pengaruh Struktur Ekonomi, Upah Minimum Provinsi, Belanja Modal, dan Investasi Terhadap Ketimpangan Pendapatan di Seluruh Provinsi di Indonesia Tahun 2005-2014 - Muara Nangarumba (Jurnal Ekonomi dan Studi Pembangunan, 2015)
Income inequality is a problem that exists in every country and a problem that continually occurs. Government, particularly in Indonesia, faced with the problems to reduce income inequality, this is because the trend of income inequality has not decreased lately, so it is feared affect the welfare of the Indonesian people. This study aimed to assess the effect of the Agricultural Sector GDP, GDP Industrial Sector, Services Sector GDP, wages Minimimum Province, Capital Expenditure and Investment Credits to Income Inequality in Indonesia in 2005 until 2014, using panel data regression. In this study the functional form of the regression model used is the model of a log-log or better known as double log, so that can know the elasticity of each independent variable on the dependent variable. The results achieved in this study, one of them is, it was found that the independent variables significantly affect income inequality with a negative effect, except variable Industrial Sector GDP. While elasticity, each independent variable inelastic to income inequality. Advanced Research also found that, according to some previous research, by improving the economic structure, raise funds for infrastructure investments multiply, increasing the minimum wage, or reduce migration can reduce the level of income inequality.Keywords: Income inequality, Regression Panel Data, Regional Economic Structures, Government Spending, Minimum Wage